SOBREPESO Y OBESIDAD EN NIÑOS Y ADOLESCENTES ASEGURADOS EN UN HOSPITAL PÚBLICO. HUÁNUCO-PERÚ - Daza Loarte, Dick (2017)
Introduction: Overweight and obesity in adolescents are experiencing, globally, a progressive increase in prevalence, which our country and even our region are not unrelated. The aim of the present study was to determine the prevalence of overweight and obesity in adolescents aged 10 to 17 years insured in the metropolitan district of Huánuco. Methods: We performed an observational prospective cross-sectional descriptive-analytic primarily to identify the overweight (BMI ≥ 85 percentile and ˂95 percentile) and obesity (BMI ≥ 95 percentile) diagnosis in adolescents; for which 387 randomly selected adolescents (195 males and 192 females) between the ages of 10 and 17, who completed a structured survey of socio-demographic and anthropometric. Results: The results show an overall prevalence of overweight in adolescents from 19.6% and obesity of 11.6%, being the prevalence, by gender as follows, 19% and 15.9% overweight and obesity in males and 20.3% and 7.3% in women, respectively (p = 0.001). Within the age group, the highest prevalence of overweight covered the ages of 10 (21.7%), 11 (19.1%), 12 (37.3%) and 13 (29.8%) years old, while for obesity covered the ages of 10 (15.2%), 11 (21.3%) and 12 (35.3%) years old (p = 0.0001). With respect to diet, physical activity, family income and type of school, overweight and obesity showed no statistically significant association. Conclusions: We conclude that the study population has a high prevalence of overweight and obesity and, predominantly the latter significantly in males, both being found more likely in younger patients.